Characterization of Briquette from Crab Shell (Portunus pelagicus) with The Addition of Pati Adhesive - Annisa; R. Marwita Sari Putri; Aidil Fadli Ilhamdy (Marinade, 2019)
Briquettes is a solid fuel that can be used as an alternative energy source which has a certain shape. This study aims to determine the effect starch adhesive material on the characteristics of briquettes from crab shells waste. the percentage used between the crab shells and the adhesive were 85%: 15%, 80%: 20%, 75%: 25% and 70%: 30%, with the size of the powder sieve 40 mesh. Mixed crab shells powder and starch produces water content of 4.34-5.25%, where the value is in conformity with the desired moisture content SNI. The addition of adhesive on crab shell briquettes generates density values ranged from 0.33-0.52 g/cm3. The content of the ash content in the shells of crabs briquettes are 45 to 68.5% and volatile matter content is generated is equal to 51.70-52.41%.